Experimental Study for Heat Transfer Characteristics of Vertical Rectangular Narrow Channels - Liu Xiaode; Tao Leren; Zheng Zhigao; Huang Lihao (Zhileng xuebao)
Ionized water was used to investigate the heat transfer characteristics of vertical rectangular narrow channels experimentally. The distribution characteristics of wall-temperature and the local heat transfer coefficient were analyzed by using single-side heating and various parameters of the working fluid. The experiment results show that the heat transfer coefficient is increased with the increase of the mass flow rate but the inlet temperature substantially has no effect on the heat transfer coefficient for convection boiling flow. When the dryness χ <0.1, the heat transfer coefficient is increased with decreases of the dryness; when the dryness χ >0.1, the heat transfer coefficient keeps constant with increases of dryness. The results also show that the heat transfer coefficient has a slight increase with the increases of dryness and is increased with the increases of inlet temperature for nucleate boiling flow.